Digital Marketing Strategies for Healthy Behaviour in Communities and Society - Erlina Puspitaloka Mahadewi; Elistia Elistia; Ayu Larasati; Dina Sudarmika; Sam Salomon; Arman Harahap (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to appraise the effectiveness of health creation through social media in encouraging healthy actions among adolescents in the health community. The discussion covers two main aspects the urgency of health creation through social media for these adolescents, the effectiveness, and challenges faced in its perpetration. The urgency of health creation through social media is grounded on the high use of digital platforms among adolescents, making it a implicit tool for propagating health information. Social media allows presto and wide access to educational content, improves health knowledge, and encourages active participation by adolescents in maintaining their health. The study results indicate that health creation through social media is effective in adding health knowledge and motivating changes in healthy hygiene actions. still, several challenges need to be addressed, similar as the spread of inaccurate information, limited access and digital knowledge, and issues of sequestration and data security within the community. The study concludes that despite these challenges, social media has great eventuality as an effective health creation tool for adolescents with applicable digital marketing. Applicable strategies are demanded to address these challenges, including digital knowledge education and the development of regulations to insure information delicacy. farther exploration is recommended to explore the combination of social media with face-to-face interventions, to enhance the effectiveness and strategies of health creation in healthy life actions.